To Paint a New Picture: Into the Lives of Eldest Siblings of Separated Fami-lies during COVID-19 - Rabuya, Daniel Andrei; Moralde, Franz Elloise; Villacampa, Angel Rose; Sagosa, Shane; Fernandez, Ravyn Bridget; Cabrera, Ralley Kyle; Cagalitan , Willem Mikkel; Bendibel, Rycel Monique; del Socorro, Celeste; Gagani, Flordeliza (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
This study emerged to enable humanitarian organizations to provide better services for children in separated families by understanding eldest siblings' lived experiences. Through Husserlian’s descriptive phenomenology utilizing Colaizzi’s method of data analysis, six participants were interviewed online at the height of the pandemic in 2021-2022 in Cebu City, Philippines. Data were transcribed using data reduction methods and revealed 6 themes: (1) "Having to always be the bigger person": Role Intensification; (2)"Devoting myself to things that weren't supposed to land on me": Adult Difficulties; (3) "Becoming stronger and keeping a soft spot"; Growing in Stature; (4) "True brothers are there for you”: The Support Given to the Supporter; (5) “To be free but mindful:'' Motivation to Persevere; (6) “To paint a better picture of life: ''Setting and Living an Example. The researchers discovered that the eldest siblings were forced to take charge of responsibilities that were not supposed to be theirs; encountered emotional difficulties such as loneliness and anxiety in facing a wide range of familial, developmental, and logistical problems; coped through these challenges with social support, religious devotion, and modern entertainment; and devoted their lives to protecting their siblings and giving them the lives they deserve. From these results, the researchers recommend that counseling is provided for the eldest siblings to enable the development of support structures and meaningful relationships that propel the eldest siblings to persevere.